Observed declines in upper ocean phosphate-to-nitrate availability - Skylar D. Gerace; Jun Yu; J. Keith Moore; Adam C. Martiny (Proceedings of the National Academy of Sciences, 2025)
Climate warming is increasing ocean stratification, which in turn should decrease the nutrient flux to the upper ocean. This may slow marine primary productivity, causing cascading effects throughout food webs. However, observing changes in upper ocean nutrients is challenging because surface concentrations are often below detection limits. We show that the nutricline depth, where nutrient concentrations reach well-detected levels, is tied to productivity and upper ocean nutrient availability. Next, we quantify nutricline depths from a global database of observed vertical nitrate and phosphate profiles to assess contemporary trends in global nutrient availability (1972–2022). We find strong evidence that the P-nutricline (phosphacline) is mostly deepening, especially throughout the southern hemisphere, but the N-nutricline (nitracline) remains mostly stable. Earth System Model (ESM) simulations support the hypothesis that reduced iron stress and increased nitrogen fixation buffer the nitracline, but not phosphacline, against increasing stratification. These contemporary trends are expected to continue in the coming decades, leading to increasing phosphorus but not nitrogen stress for marine phytoplankton, with important ramifications for ocean biogeochemistry and food web dynamics.